High temperature cyclic oxidation behavior of a low manganese Fe12Mn9Cr5Si4Ni-NbC shape memory stainless steels - de Sousa Malafaia, Artur Mariano; da Silva, Rodrigo; Della Rovere, Carlos Alberto; Baldan, Renato [UNESP]; Suárez-Fernández, Lucía; Cabrera-Marrero, José-María; de Oliveira, Marcelo Falcão (Elsevier, 2021)
High amounts of Mn in Fe-Mn-Si-Cr-Ni shape memory stainless steels are detrimental for oxidation resistance at high temperatures. However, in order to maintain the shape memory effect of these alloys the content of manganese must be between 12 and 19 wt%. Thus, this study evaluated an alloy with relative low Mn (12 wt%) in cyclic oxidation tests at 800, 900 and 1000 °C. Kinetic analysis demonstrated parabolic oxidation behavior with rate similar to higher Mn-containing alloys from literature. It was also observed internal oxidation, for the first time in these alloys, and oxide layers composed by Mn2O3 and Mn-Cr spinel at 800 °C as well as Mn-Cr spinel and no continuous silica at 1000 °C. The internal oxidation mechanism was related to oxide layer defects and not to partial oxygen pressure decrease, considering that the internal oxidation presented the same oxides of the external layer. These results show that low Mn content does not improve the use viability of these alloys at high temperatures, since no decreasing in oxidation rate was observed and further internal oxidation occurred.
Keywords: Fe-Mn-Si-Cr-Ni; High temperature oxidation; Internal oxidation; Manganese effect; Silica